A method of preparing mineralized collagen casings by wet infusion

CN117717108BActive Publication Date: 2026-10-27YIXING INST OF FOOD & BIOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311607897.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2026-10-27
Estimated Expiration
2043-11-29

Smart Images

  • Figure CN117717108B_ABST
    Figure CN117717108B_ABST
Patent Text Reader

Abstract

The application discloses a kind of wet soaking preparation mineralized collagen intestine, which includes the following steps, dissolving edible polymer and calcium salt, adding phosphate, forming polymer-calcium phosphate complex suspension;Mix the acid liquid with the cowhide pulp, make the glue group, and stand still;After extrusion, the glue group is immersed in lye to solidify;After solidification, the glue group is washed with water, plasticized, dried, and then wet, to obtain mineralized collagen intestine. Through mineralization means, the problem of further improvement of the current technical field of casing is realized, and the performance of the casing product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of collagen casing processing technology, and in particular to a method for preparing mineralized collagen casings by wet soaking. Background Technology

[0002] Sausage casings, used as outer packaging for sausages, serve to block air and extend the shelf life of meat products. Natural casings, primarily made from pig or sheep intestines, were the earliest type of natural casings used. However, with the expansion of the sausage market, the supply of natural casings gradually fell short of demand, leading to the development of various artificial casings.

[0003] Artificial sausage casings include cellulose casings, plastic casings, and artificial collagen casings. Artificial collagen casings, due to their similarity to natural casings, are gradually gaining a dominant position in the market. The preparation methods for artificial collagen casings are divided into dry and wet methods. The dry method directly extrudes ground and crushed collagen fibers to form collagen casings. The wet method further disperses the crushed collagen fibers through acid swelling, obtaining finer and more uniform collagen fibers. After the collagen particles are extruded and shaped, they are then soaked in an aqueous solution for shaping, cross-linking, and plasticizing, and finally dried to obtain the finished collagen casing. Compared to the dry method, collagen casings prepared by the wet method are often more uniformly modified, have a softer and more delicate texture, and better permeability, making them popular with consumers. However, the wet process results in a higher moisture content in the wet collagen membrane, which leads to insufficient strength in the casings, making them prone to problems such as slippage, easy breakage during enema, and poor cooking performance.

[0004] Collagen mineralization, a biomimetic technique inspired by human skeletal structure, can introduce calcium phosphate into the interior of collagen fibers, thereby enhancing the wet mechanical properties of artificial collagen casings. Summary of the Invention

[0005] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.

[0006] In view of the problems existing in the above and / or existing collagen casing products, the present invention is proposed.

[0007] Therefore, as one aspect of the present invention, the present invention overcomes the deficiencies existing in the prior art and proposes a method for preparing mineralized collagen casings by wet soaking.

[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution: A method for preparing mineralized collagen casings by wet soaking, characterized by comprising the following steps: Dissolve edible polymers and calcium salts, add phosphates to form a polymer-calcium phosphate complex suspension; The acid solution was mixed with the cowhide paste to form a gel, which was then left to stand. After extrusion, the gel pellets are immersed in an alkaline solution to cure. After the solidified collagen flocs are washed with water, plasticized and mineralized, dried and rehydrated to obtain mineralized collagen casings.

[0009] As a preferred embodiment of the wet soaking method for preparing mineralized collagen casings according to the present invention, it includes: the edible polymer being sodium carboxymethyl cellulose.

[0010] As a preferred embodiment of the wet soaking method for preparing mineralized collagen casings according to the present invention, it includes: calcium salts being anhydrous calcium chloride and calcium lactate.

[0011] As a preferred embodiment of the wet soaking method for preparing mineralized collagen casings according to the present invention, it includes: the phosphate being disodium hydrogen phosphate, diammonium hydrogen phosphate, or dipotassium hydrogen phosphate.

[0012] As a preferred embodiment of the wet soaking method for preparing mineralized collagen casings according to the present invention, it includes: an edible polymer content of 0.1-1.5%.

[0013] As a preferred embodiment of the wet soaking method for preparing mineralized collagen casings according to the present invention, it includes: a calcium salt content of 6-14 mM.

[0014] As a preferred embodiment of the wet soaking method for preparing mineralized collagen casings according to the present invention, it includes: a phosphate content of 2-10 mM.

[0015] As a preferred embodiment of the wet soaking method for preparing mineralized collagen casings according to the present invention, it includes: sodium carboxymethyl cellulose with a molecular weight of 250 kDa or 100 kDa.

[0016] As a preferred embodiment of the wet soaking method for preparing mineralized collagen casings according to the present invention, it includes: sodium carboxymethyl cellulose having a degree of substitution of 1.2, 0.9 or 0.7.

[0017] This invention provides a method for preparing mineralized collagen casings by wet soaking. By mineralizing the collagen membrane, the internal structure of the water-absorbing collagen membrane becomes more compact, thereby enhancing the wet tensile strength and elongation at break of the collagen membrane. Attached Figure Description

[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein: Figure 1 Wet tensile strength and elongation at break of mineralized films with different calcium salt types and concentrations; Figure 2 Wet tensile strength and elongation at break of mineralized films with different phosphate types and concentrations; Figure 3 Wet tensile strength and elongation at break of membranes treated with sodium carboxymethyl cellulose at different concentrations and mineralized membranes treated with different concentrations of the composite were measured. Figure 4 Cross-sectional scanning electron microscope images of collagen membranes mineralized with CMC-ACP at different concentrations; Figure 5 Collagen membranes treated with different concentrations of sodium carboxymethyl cellulose; Figure 6 Collagen membranes treated with sodium carboxymethyl cellulose-calcium phosphate complex at different concentrations. Detailed Implementation

[0019] To make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to specific examples.

[0020] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.

[0021] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.

[0022] Unless otherwise specified, the sodium carboxymethyl cellulose used in this invention has a molecular weight of 250 kDa and a degree of substitution of 1.2; the cowhide paste prepared in each embodiment uses 40 g of cowhide granules (1 cm) 3 Small pieces (from Beijing Qiushi Sausage Casing Co., Ltd.) were mixed with 100g of ice and placed in a crusher (DFY-200C, Wenling Linda Machinery Co., Ltd.). The machine was started and crushed for 18 seconds, then stopped for 18 seconds. This process was repeated 5 times to obtain cowhide pulp.

[0023] In this embodiment of the invention, the mechanical properties were determined as follows: the mechanical properties of the collagen membrane under wet conditions were measured using a texture analyzer (TA.XT2i, Lloyd Instruments, UK) equipped with an A / MTG probe. Tensile strength (TS) and elongation at break (EAB) were calculated using the following equations:

[0024] Where Fmax is the maximum force when the film breaks, L is the length when the film breaks, L0 is the initial length of the film between the initial gaps, F is the force that stretches the film, Thickness is the film thickness, which is the average thickness of five randomly measured points on the film, and width is the film width, which is 1 cm.

[0025] Example 1: 1. Preparation of plasticizing mineralizing solution: Weigh a certain amount of sodium carboxymethyl cellulose powder and slowly add it to water while stirring to form a 0.2% sodium carboxymethyl cellulose aqueous solution; then add a certain amount of calcium salt (anhydrous sodium chloride) and stir until the calcium salt is completely dissolved, so that the calcium salt concentration is 10mM; finally add a certain amount of phosphate (disodium hydrogen phosphate) and stir until the phosphate is completely dissolved, so that the phosphate concentration is 6mM. 2. Preparation of colloids: 40g of cowhide granules were mixed with 100g of ice and crushed to make cowhide paste. An equal mass of 0.35wt% hydrochloric acid solution was mixed with the cowhide paste to prepare colloids, which were then stored at 4℃ for 18h. 3. Extrusion curing: The gel pellets are extruded through an extruder at a speed of 20 rpm to become sausage casings. The sausage casings are then immersed in 4.4 wt% ammonia water for curing at room temperature for 10 minutes. After curing, the sausage casings are transferred to a clean water tank and washed with running water for 30 minutes. 4. Plasticization and mineralization: The washed sausage casings are transferred to the plasticization and mineralization solution prepared in (1) for plasticization and mineralization. The reaction time is 30 min. 5. Drying and rehumidification: After removing excess liquid from the surface of the casing, place the casing at room temperature to air dry. After air drying, use a rehumidification device to control the humidity at 15% to obtain mineralized collagen casing.

[0026] Example 2: To further improve the wet mechanical properties of mineralized collagen casings and highlight the influence of calcium salt type on these properties, the same preparation parameters as in Example 1 were used to analyze the effect of calcium salt type on the wet mechanical properties of mineralized collagen casings. 1. Preparation of plasticizing mineralizing solution: Weigh a certain amount of sodium carboxymethyl cellulose powder and slowly add it to water while stirring to form a 0.2% wt sodium carboxymethyl cellulose aqueous solution; then add a certain amount of calcium salt (anhydrous calcium chloride, calcium lactate) and stir until the calcium salt is completely dissolved; finally add a certain amount of disodium hydrogen phosphate (phosphate) and stir until the phosphate is completely dissolved. 2. Preparation of micelles: 40g of cowhide granules (Beijing Qiushi Collagen Casing Co., Ltd.) were mixed with 100g of ice and crushed to make cowhide paste. 0.35wt% hydrochloric acid solution was mixed with an equal mass of cowhide paste to prepare micelles, which were stored at 4℃ for 18h. 3. Extrusion curing: The gel pellets are extruded through an extruder at a speed of 20 rpm to become sausage casings. The sausage casings are then immersed in 4.4 wt% ammonia water for curing at room temperature for 10 minutes. After curing, the sausage casings are transferred to a clean water tank and washed with running water for 30 minutes. 4. Plasticization and mineralization: The washed sausage casings are transferred to the plasticization and mineralization solution prepared in (1) for plasticization and mineralization. The reaction time is 30 min. 5. Drying and rehumidification: After removing excess liquid from the surface of the casing, place the casing at room temperature to air dry. After air drying, use a rehumidification device to control the humidity at 15% to obtain mineralized collagen casing.

[0027] Example 3: To further improve the wet mechanical properties of mineralized collagen casings and highlight the effect of calcium salt concentration on these properties, the same preparation parameters as in Example 1 were used to analyze the influence of calcium salt concentration on the wet mechanical properties of mineralized collagen casings. 1. Preparation of plasticizing mineralizing solution: Weigh a certain amount of sodium carboxymethyl cellulose powder and slowly add it to water while stirring to form a 0.2% wt sodium carboxymethyl cellulose aqueous solution; then add a certain amount of calcium salt (6-14 mM) and stir until the calcium salt is completely dissolved; finally add a certain amount of disodium hydrogen phosphate (phosphate) and stir until the phosphate is completely dissolved. 2. Preparation of micelles: 40g of cowhide granules (Beijing Qiushi Collagen Casing Co., Ltd.) were mixed with 100g of ice and crushed to make cowhide paste. 0.35wt% hydrochloric acid solution was mixed with an equal mass of cowhide paste to prepare micelles, which were stored at 4℃ for 18h. 3. Extrusion curing: The gel pellets are extruded through an extruder at a speed of 20 rpm to become sausage casings. The sausage casings are then immersed in 4.4 wt% ammonia water for curing at room temperature for 10 minutes. After curing, the sausage casings are transferred to a clean water tank and washed with running water for 30 minutes. 4. Plasticization and mineralization: The washed sausage casings are transferred to the plasticization and mineralization solution prepared in (1) for plasticization and mineralization. The reaction time is 30 min. 5. Drying and rehumidification: After removing excess liquid from the surface of the casing, place the casing at room temperature to air dry. After air drying, use a rehumidification device to control the humidity at 15% to obtain mineralized collagen casing.

[0028] The tensile strength and elongation at break of mineralized collagen casings prepared with different types of calcium salts were measured, and the data were recorded in [the relevant database]. Figure 1 middle.

[0029] Depend on Figure 1 It can be seen that the casings made of anhydrous calcium chloride have better wet tensile strength and elongation at break than the casings made of calcium lactate. As the amount of calcium chloride used increases, the wet tensile strength of the casings first increases and then decreases, while the elongation at break remains basically the same and then decreases. 10 mM is the preferred concentration of calcium chloride.

[0030] Example 4: To further improve the wet mechanical properties of mineralized collagen casings and highlight the influence of phosphate type on these properties, the same preparation parameters as in Example 1 were used to analyze the effect of phosphate type on the wet mechanical properties of mineralized collagen casings. 1. Preparation of plasticizing mineralizing solution: Weigh a certain amount of sodium carboxymethyl cellulose powder and slowly add it to water while stirring to form a 0.2% wt sodium carboxymethyl cellulose aqueous solution; then add a certain amount of calcium salt (10 mM anhydrous calcium chloride) and stir until the calcium salt is completely dissolved; finally add a certain amount of phosphate (disodium hydrogen phosphate, diammonium hydrogen phosphate, dipotassium hydrogen phosphate) and stir until the phosphate is completely dissolved. 2. Preparation of micelles: 40g of cowhide granules (Beijing Qiushi Collagen Casing Co., Ltd.) were mixed with 100g of ice and crushed to make cowhide paste. 0.35wt% hydrochloric acid solution was mixed with an equal mass of cowhide paste to prepare micelles, which were stored at 4℃ for 18h. 3. Extrusion curing: The gel pellets are extruded through an extruder at a speed of 20 rpm to become sausage casings. The sausage casings are then immersed in 4.4 wt% ammonia water for curing at room temperature for 10 minutes. After curing, the sausage casings are transferred to a clean water tank and washed with running water for 30 minutes. 4. Plasticization and mineralization: The washed sausage casings are transferred to the plasticization and mineralization solution prepared in (1) for plasticization and mineralization. The reaction time is 30 min. 5. Drying and rehumidification: After removing excess liquid from the surface of the casing, place the casing at room temperature to air dry. After air drying, use a rehumidification device to control the humidity at 15% to obtain mineralized collagen casing.

[0031] Example 5: To further improve the wet mechanical properties of mineralized collagen casings and highlight the effect of phosphate concentration on these properties, the same preparation parameters as in Example 1 were used to analyze the influence of phosphate concentration on the wet mechanical properties of mineralized collagen casings. 1. Preparation of plasticizing mineralizing solution: Weigh a certain amount of sodium carboxymethyl cellulose powder and slowly add it to water while stirring to form a 0.2% wt sodium carboxymethyl cellulose aqueous solution; then add a certain amount of calcium salt (10 mM anhydrous calcium chloride) and stir until the calcium salt is completely dissolved; finally add a certain amount of phosphate (2-10 mM phosphate) and stir until the phosphate is completely dissolved. 2. Preparation of micelles: 40g of cowhide granules (Beijing Qiushi Collagen Casing Co., Ltd.) were mixed with 100g of ice and crushed to make cowhide paste. 0.35wt% hydrochloric acid solution was mixed with an equal mass of cowhide paste to prepare micelles, which were stored at 4℃ for 18h. 3. Extrusion curing: The gel pellets are extruded through an extruder at a speed of 20 rpm to become sausage casings. The sausage casings are then immersed in 4.4 wt% ammonia water for curing at room temperature for 10 minutes. After curing, the sausage casings are transferred to a clean water tank and washed with running water for 30 minutes. 4. Plasticization and mineralization: The washed sausage casings are transferred to the plasticization and mineralization solution prepared in (1) for plasticization and mineralization. The reaction time is 30 min. 5. Drying and rehumidification: After removing excess liquid from the surface of the casing, place the casing at room temperature to air dry. After air drying, use a rehumidification device to control the humidity at 15% to obtain mineralized collagen casing.

[0032] The tensile strength and elongation at break of mineralized collagen casings prepared with different types of phosphates were determined, and the data were recorded. Figure 2 middle.

[0033] Depend on Figure 2 It can be seen that casings made from disodium hydrogen phosphate have better wet tensile strength and elongation at break than casings made from other types of phosphates. As the amount of disodium hydrogen phosphate used increases, the wet tensile strength and elongation at break of the casings first increase and then decrease. 8 mM is the preferred concentration of calcium chloride.

[0034] Example 6: To further improve the wet mechanical properties of mineralized collagen casings and highlight the effect of edible stabilizer concentration on their wet mechanical properties, the same preparation parameters as in Example 1 were used to analyze the effect of edible polymer concentration on the wet mechanical properties of mineralized collagen casings. 1. Preparation of plasticizing mineralizing solution: Weigh a certain amount of sodium carboxymethyl cellulose powder and slowly add it to water while stirring to form 0.1%, 0.2%, 0.25%, 0.5%, 0.75%, 1.0%, and 1.5% wt sodium carboxymethyl cellulose aqueous solutions; then add a certain amount of anhydrous calcium chloride (calcium salt) and stir until the calcium salt is completely dissolved, so that the calcium salt concentration is 10 mM; finally, add a certain amount of disodium hydrogen phosphate (phosphate) and stir until the phosphate is completely dissolved, so that the phosphate concentration is 6 mM. 2. Preparation of micelles: 40g of cowhide granules (Beijing Qiushi Collagen Casing Co., Ltd.) were mixed with 100g of ice and crushed to make cowhide paste. 0.35wt% hydrochloric acid solution was mixed with an equal mass of cowhide paste to prepare micelles, which were stored at 4℃ for 18h. 3. Extrusion curing: The gel pellets are extruded through an extruder at a speed of 20 rpm to become sausage casings. The sausage casings are then immersed in 4.4 wt% ammonia water for curing at room temperature for 10 minutes. After curing, the sausage casings are transferred to a clean water tank and washed with running water for 30 minutes. 4. Plasticization and mineralization: The washed sausage casings are transferred to the plasticization and mineralization solution prepared in (1) for plasticization and mineralization. The reaction time is 30 min. 5. Drying and rehumidification: After removing excess liquid from the surface of the casing, place the casing at room temperature to air dry. After air drying, use a rehumidification device to control the humidity at 15% to obtain mineralized collagen casing.

[0035] The tensile strength and elongation at break of mineralized collagen casings prepared with different concentrations of sodium carboxymethyl cellulose were determined, and the data were recorded. Figure 3 The scanning electron microscope (SEM) image of the interface section of the finished product is shown below. Figure 4 As shown.

[0036] Depend on Figure 3 It can be seen that the casings made from sodium carboxymethyl cellulose-calcium phosphate complex have better wet tensile strength and elongation at break. As the amount of sodium carboxymethyl cellulose used increases, the wet tensile strength of the casing first increases, then decreases, and then increases again, while the elongation at break first increases, then decreases, and then increases again. Preferably, 0.5% is the preferred concentration of sodium carboxymethyl cellulose.

[0037] Cross-sectional scanning electron microscope images of CMC-ACP mineralized collagen membranes of different concentrations are shown below. Figure 4 As shown, a physical image of the fabricated membrane is as follows. Figure 6 As shown, from Figure 5 It can be seen that as the CMC concentration increases, the pores in the collagen membrane gradually increase, leading to a weakening of the wet mechanical properties of the collagen membrane. Mineralization treatment can make the internal structure of the collagen membrane more compact, and as the CMC concentration increases, larger pores only appear in the 1.0% and 1.5% groups compared to the CMC group.

[0038] Comparative Example 1: Omit the calcium chloride and disodium hydrogen phosphate added in Example 6, and prepare collagen casings using the following steps: 1. Preparation of plasticizing solution: Weigh a certain amount of sodium carboxymethyl cellulose powder and slowly add it to water while stirring to form 0.1%, 0.2%, 0.25%, 0.5%, 0.75%, 1.0%, and 1.5% wt sodium carboxymethyl cellulose aqueous solutions; 2. Preparation of micelles: 40g of cowhide granules (Beijing Qiushi Collagen Casing Co., Ltd.) were mixed with 100g of ice and crushed to make cowhide paste. 0.35wt% hydrochloric acid solution was mixed with an equal mass of cowhide paste to prepare micelles, which were stored at 4℃ for 18h. 3. Extrusion curing: The gel pellets are extruded through an extruder at a speed of 20 rpm to become sausage casings. The sausage casings are then immersed in 4.4 wt% ammonia water for curing at room temperature for 10 minutes. After curing, the sausage casings are transferred to a clean water tank and washed with running water for 30 minutes. 4. Plasticization and mineralization: The washed sausage casings are transferred to the plasticization and mineralization solution prepared in (1) for plasticization and mineralization. The reaction time is 30 min. 5. Drying and rehumidification: After removing excess liquid from the surface of the casing, place the casing at room temperature to air dry. After air drying, use a rehumidification device to control the humidity at 15% to obtain mineralized collagen casing.

[0039] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing mineralized collagen casings by wet soaking, characterized in that: include, Preparation of plasticizing and mineralizing solution: Dissolve edible polymer and calcium salt, add phosphate to form a polymer-calcium phosphate complex suspension, wherein the edible polymer is sodium carboxymethyl cellulose, the calcium salt is anhydrous calcium chloride, the phosphate is disodium hydrogen phosphate, the calcium salt content is 10 mM, the phosphate content is 8 mM, the edible polymer content is 0.5 wt%, and the molecular weight of sodium carboxymethyl cellulose is 250 kDa or 100 kDa; The acid solution was mixed with the cowhide paste to form a gel, which was then left to stand. After the gel pellets are extruded, they are immersed in an alkaline solution to cure. After the cured collagen pellets are washed with water, they are transferred to a plasticizing and mineralizing solution for plasticizing and mineralizing, dried and rehydrated to obtain mineralized collagen casings. The reaction time for plasticizing and mineralizing is 30 minutes.

2. The method for preparing mineralized collagen casings by wet soaking as described in claim 1, characterized in that: The degree of substitution of the sodium carboxymethyl cellulose is 1.2, 0.9, or 0.7.

Citation Information

Patent Citations

  • Preparation method of bionic mineralized collagen scaffold

    CN107929812A

  • Preparation method of deep-fried collagen casings

    CN113475559A